2014
DOI: 10.1371/journal.pone.0102665
|View full text |Cite
|
Sign up to set email alerts
|

De Novo Assembly and Transcriptome Analysis of the Rubber Tree (Hevea brasiliensis) and SNP Markers Development for Rubber Biosynthesis Pathways

Abstract: Hevea brasiliensis (Willd. Ex Adr. Juss.) Muell.-Arg. is the primary source of natural rubber that is native to the Amazon rainforest. The singular properties of natural rubber make it superior to and competitive with synthetic rubber for use in several applications. Here, we performed RNA sequencing (RNA-seq) of H. brasiliensis bark on the Illumina GAIIx platform, which generated 179,326,804 raw reads on the Illumina GAIIx platform. A total of 50,384 contigs that were over 400 bp in size were obtained and sub… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
66
3

Year Published

2016
2016
2021
2021

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 82 publications
(78 citation statements)
references
References 62 publications
9
66
3
Order By: Relevance
“…We obtained 7,588 (21.62 %) unigenes that were longer than 1 kb, a size range that commonly confers a high annotation rate [34, 55]. We also compared the unigene metrics obtained here to the transcriptomes that were obtained from Phytozome (Additional file 1) and found that the observed total contig number, N50 contig length, average contig length and GC content more closely resembled the Phytozome transcriptomes of these species.…”
Section: Resultsmentioning
confidence: 90%
See 1 more Smart Citation
“…We obtained 7,588 (21.62 %) unigenes that were longer than 1 kb, a size range that commonly confers a high annotation rate [34, 55]. We also compared the unigene metrics obtained here to the transcriptomes that were obtained from Phytozome (Additional file 1) and found that the observed total contig number, N50 contig length, average contig length and GC content more closely resembled the Phytozome transcriptomes of these species.…”
Section: Resultsmentioning
confidence: 90%
“…Similar to other perennial species [55], Koronivia grass remains in the early stages of domestication, which increases the difficulty of identifying concentrated gene groups that play specific roles in important agronomic characteristics. The Koronivia grass breeding program has applied selection methods for many decades, and hybrid progenies were obtained in the early 2000s.…”
Section: Resultsmentioning
confidence: 99%
“…In this study, we achieved more than 7 Gb of clean reads from each of the four sets of sequencing samples derived from the cambia-containing materials of rubber tree clone CATAS7-33-97. The sequencing depth of each sample was higher than the reported 0.2–6 Gb sequencing depth of bark in rubber tree3031323334 and equivalent to sequencing depth (7–8 Gb) reported by Mantello et al 35. This high sequencing depth is beneficial for global transcriptome assembly.…”
Section: Discussionmentioning
confidence: 62%
“…Fetrina Oktavia et al: IRRDB 1981 Diversity and Population Structure............................................................................. The ability to identify genetic resources having wide genetic distances would be beneficial in the identification of parents for hybridization programs since crossing among those parents' result in in more diverse progenies and prevent the occurrence of the inbreeding depression. Inbreeding depression was the major problem in the current rubber trees breeding program (Lopes & Marques, 2015). Taken together, based on the genetic diversity and the population analysis results using EST-SSR primers, we could summarize that the genetic structure of the evaluated PN'81 rubber accessions was more widely and diverse than that of the Wickham clones.…”
Section: Genetic Structure Of Populationmentioning
confidence: 85%
“…Moreover, because of assortative mating, low fruit-set limitation, selection for the high latex yield character, and extensive use of particular clones as parents in rubber breeding programs, further reduce the genetic diversity of the commercial rubber germplasm (Priyadarshan, 2016). Researchers have reported the occurrences of inbreeding depression because the superior genotypes are repeatedly used in rubber tree breeding programs, resulting in low latex yield, high-risk exposures to disease and insects attack (Lopes & Marques, 2015), and low adaptability to environmental changes (Ellstrand & Elam, 1993). Therefore, broadening the genetic basis through the introduction of new germplasm from the natural population is necessary for the breeding program.…”
Section: Introductionmentioning
confidence: 99%